Warming substantially amplifies Antarctic coastal polynyas as key carbon sinks - Chengzhen Zhou; Maodian Liu; Brad E. Rosenheim; Thomas S. Bianchi; Nikki H. Zhang; Xingrui Cai; Qianru Zhang; Xuejun Wang (Proceedings of the National Academy of Sciences, 2025)
The Southern Ocean plays an important role in the global carbon cycle by absorbing atmospheric CO 2 , aiding climate change mitigation. Antarctic coastal polynyas (ACPs) are key CO 2 uptake areas, yet whether this CO 2 is effectively sequestered as organic carbon (OC) in marine sediments, and the spatiotemporal dynamics and drivers of this process, remains unclear. Here, we reconstruct a high-resolution record of Holocene (~12,000 y BP) to present-day OC accumulation fluxes and sources in ACP sediments using existing data as well as our measurements. We find that despite covering only 3% of the Southern Ocean, ACPs account for approximately 42% of the modern OC accumulation across the Southern Ocean. Since the Holocene, OC accumulation has increased ninefold due to climate warming, largely driven by marine primary production. Structural equation modeling reveals that warming enhances the biological carbon pump and OC accumulation efficiency by expanding and prolonging open water areas in ACPs, with larger ACPs showing stronger feedback. Furthermore, basal melt from ice shelves releases fine particulate matter, further boosting OC accumulation. Our findings highlight that climate warming has greatly amplified ACPs’ carbon-sequestration efficiency, making them rapidly expanding and crucial carbon sinks in the Southern Ocean, with the potential to provide strong negative feedback in future climate change.